2018
DOI: 10.1016/j.hbrcj.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigating climate responsive solutions in vernacular architecture of Bushehr city

Abstract: As the main concern in sustainability is consideration to climatic conditions, climatically compatible design is the closest way of getting the maximum advantage of renewable sources of energy, while at the same time the design minimizes the undesirable effects of the construction in the environment and causes coordination with sustainability. From this point of view, the Bushehr traditional fabric, which is located in northern side of the Persian Gulf shore in south of Iran, is distinguished as a city with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 4 publications
1
34
0
Order By: Relevance
“…Vernacular architectures across continents are widely understood to include several strategies to act in response to local climatic conditions, which among others reduce thermal deviations from comfort temperatures, such as thermal storage, earth coupling, natural ventilation strategies, spatial programmatic layout, night cooling, vegetation, colouration, and more [3][4][5][6]. The strategies in focus 2 of 12 here are operable elements for the regulation of solar radiation, which significantly contribute via the radiant temperature to the perceived operative temperature [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Vernacular architectures across continents are widely understood to include several strategies to act in response to local climatic conditions, which among others reduce thermal deviations from comfort temperatures, such as thermal storage, earth coupling, natural ventilation strategies, spatial programmatic layout, night cooling, vegetation, colouration, and more [3][4][5][6]. The strategies in focus 2 of 12 here are operable elements for the regulation of solar radiation, which significantly contribute via the radiant temperature to the perceived operative temperature [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons between traditional and contemporary houses have indicated that traditional houses, which employ building design strategies, are more compatible with the environment, resulting in better thermal comfort in indoor spaces. Although in contemporary houses many technologies are used to achieve indoor thermal comfort [9][10][11], several studies have indicated that passive and climatic strategies used in traditional buildings can be implemented in modern buildings [12].…”
Section: Introductionmentioning
confidence: 99%
“…Bushehr is considered the most important port near the Persian Gulf border. Although in recent years many transformations have occurred in this city and its urban public spaces, its vernacular fabric is unique and has been formed based on its climate position [26]. Vernacular residents in this region used some climate-adapted solutions to protect their buildings from the harsh outside climate.…”
Section: Introductionmentioning
confidence: 99%
“…They built their houses based on minimum sunlight penetration and the optimal usage of wind currents with several solutions. Climatic solutions in Bushehr vernacular architecture include: orientation of buildings with consideration of wind flow direction for the maximum use of the gentle cool breezes, central organization of spaces for creating proper ventilation, the existence of windows toward the central courtyard and toward alleys for producing transverse ventilation, use of vernacular elements for shading like Shenashir (in Figure 2), use of materials with low heat capacity for adaptability to hot and humid climates, and use of rooftops at nights for the maximum use of the wind draft [26]. The ground floors of these vernacular dwellings were used in the relatively colder seasons, January and February, to prevent cold winds through winter spaces, and along with the winter spaces, there were also other service spaces such as kitchens, storage areas, and bathrooms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation